An assessment of how well social movement theory explains the emergence and development of Rape Crisis Cape Town - Cook, Alison (Department of Political Studies, 2023)
This thesis uses three social movement theories to analyse the growth and development of Rape Crisis Cape Town (Rape Crisis). Rape Crisis provides counselling to rape victims, education and advocacy. The thesis also uses Rape Crisis to assess the analytic power of these theories, which were developed in the USA and Europe, in South Africa. This thesis seeks answers to several key questions about Rape Crisis's history. It emerged in 1976 at a time when there was relatively little self-conscious feminist activity in South Africa. How was Rape Crisis able to emerge and grow despite hostility from authorities and other left wing organisations; why Rape Crisis went from a modified collective to a collective when feminist organisations usually follow the opposite path; why Rape Crisis maintained its collective structure for much longer than most feminist organisations; why Rape Crisis changed dramatically in terms of structure and organisational culture after 1992? This work uses interviews, documentary evidence, and secondary sources to build a picture of Rape Crisis's development and the issues it confronted. The thesis covers the period 1976 to 2000. The main chapters consider a phase of Rape Crisis's development using the three social movement theories under consideration: resource mobilisation theory, political process theory and generational theory. The analytical power of each theory is considered. The thesis concludes that the theories considered offer a cogent analysis of Rape Crisis and combining the theories creates a strong analysis. The theories were able to provide answers to the key questions outlined above. The shortfalls identified in the theories were not caused because the theories were unsuitable for examining an organisation in South Africa. The problems stemmed from the failure of the theories to consider the impact of emotion on organisations. Thus, the criticism is applicable to these theories whenever they are dealing with social movement organisations that engage in emotional work. The key emotions for the purposes of this thesis were stress and those associated with trauma. These emotions impacted on decision-making, organisational structure and collective identity. However, the thesis concludes that the existing theories can be adapted to consider the impact of emotion. Rape Crisis's ability to emerge and grow without a sponsor organisation challenges the theories' arguments about the importance of social movement organisations being based in organisationally rich social sectors.